2000
DOI: 10.1097/00005537-200010000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Autogenous Cartilage in the Shape of a Helix Using an Injectable Hydrogel Scaffold

Abstract: Objective: Previous successful efforts to tissue engineer cartilage for an auricle have used an immunocompromised nude mouse xenograft model. Subsequent efforts in an immunocompetent autogenous animal model have been less successful because of an inflammatory response directed against the foreign scaffold polymer used to provide an auricular shape. We studied an alternative polymer material and surgical technique to engineer autogenous cartilage in the shape of a human ear helix using injectable hydrogel scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(70 citation statements)
references
References 17 publications
1
69
0
Order By: Relevance
“…Hydrogels are a class of materials that satisfy the requirements for a successful injectable TE system. Examples of injectable hydrogel systems that have been employed in TE include Pluoronics®, a block copolymer of polyethylene glycopolypropylene glycol [187], collagen [166], Matrigel TM [188], an ECM extract derived from a solubilized basement membrane preparation extracted from EHS mouse sarcoma, and fibrin glue [189]. The injectable polymer systems that crosslink via physical interactions are simple to apply as no external initiator or cross linking agent is required for the hydrogel formation.…”
Section: Scaffoldsmentioning
confidence: 99%
“…Hydrogels are a class of materials that satisfy the requirements for a successful injectable TE system. Examples of injectable hydrogel systems that have been employed in TE include Pluoronics®, a block copolymer of polyethylene glycopolypropylene glycol [187], collagen [166], Matrigel TM [188], an ECM extract derived from a solubilized basement membrane preparation extracted from EHS mouse sarcoma, and fibrin glue [189]. The injectable polymer systems that crosslink via physical interactions are simple to apply as no external initiator or cross linking agent is required for the hydrogel formation.…”
Section: Scaffoldsmentioning
confidence: 99%
“…Pluronic 1 F127 is a US Food and Drug Administration-approved nonionic surfactant/excipient used in inhalation, oral, and ophthalmic preparations with published safety data [3]. Injectable formulations have been investigated in animals [2,12,13]. Pluronic 1 F127 has high affinity for both water and MMA.…”
Section: Discussionmentioning
confidence: 99%
“…24 The combination of MSCs and thermoreversible PF127 gel can be easily delivered using an 18-gauge needle. 21,22 It has been suggested that PF127 can enhance early wound healing in third-degree burns; it has also been considered as a carrier for osseous graft materials and growth factors. 25 PF127 facilitated the spread, attachment and growth of human gingival fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…PF127 has been shown to facilitate the early attachment of human gingival fibroblasts and increase their growth rate, 20 and has also proven advantageous in cartilage tissue engineering. 21,22 The aim of this study was to investigate the regeneration ability of osseous tissue and the periodontal attachment apparatus in surgically created transgingival periodontal defects following implantation of autologous MSCs engineered ex vivo to express the BMP-2 gene and using PF127 as a scaffold.…”
Section: Introductionmentioning
confidence: 99%